Three-Component Syntheses of Functionalized Selenocyanates - Ostapiuk, Yurii V.; Barabash, Oksana V.; Ostapiuk, Mary Y.; Herzberger, Colin; Plieth, Mattes; Schmidt, Andreas (Synthesis, 2024)
A metal-free Meerwein-type arylation protocol of α,β-unsaturated compounds is reported. 4-Aryl-3-selenocyanatobutan-2-ones, methyl 3-aryl-2-selenocyanatopropanoates, 3-aryl-2-selenocyanatopropanenitriles, and 1-aryl-2-phenyl-2-selenocyanatoethanes were prepared by a selenocyanatoarylation reaction from easily available arenediazonium tetrafluoroborates, potassium selenocyanate, and methyl vinyl ketone, methyl acrylate, acrylonitrile, or styrene, respectively, in 39–84% yields. The reaction proceeds smoothly and quickly under mild reaction conditions. The reaction can be scaled to the gram scale. A mechanism for this reaction is proposed.
Keywords: Meerwein reaction; arenediazonium salts; radicals; selenium; 77Se NMR